A chemical sand-fixing material and its use method

A chemical sand-fixing material with polyquaternium and additives forms a durable shell on sand surfaces, addressing desert environmental challenges by providing thermal stability and erosion resistance, thus promoting ecological restoration.

CN115505400BActive Publication Date: 2024-12-31SICHUAN HAINA YONGGU TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202211194751.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-28
Publication Date
2024-12-31
Estimated Expiration
2042-09-28

AI Technical Summary

Technical Problem

Existing chemical sand-fixing materials fail to meet the requirements of desert environments due to high temperature, water shortage, high salt content, and strong winds, leading to inadequate wind erosion resistance, high temperature resistance, and crust strength, limiting their application in desert areas.

Method used

A chemical sand-fixing material composed of polyquaternium, carboxymethyl cellulose, polymaleic anhydride, gelatin, polyvinyl alcohol, polyethylene glycol, and polyacrylamide, optionally with additives like antioxidants and ultraviolet light absorbers, is dissolved in water and sprayed onto quicksand to form a durable, high-strength shell layer.

Benefits of technology

The material provides excellent thermal stability, wind erosion resistance, and durability, forming a thick shell that effectively stabilizes sand surfaces, enhancing desert ecological restoration.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a chemical sand-fixing material and a method for using the same, wherein the chemical sand-fixing material comprises the following components: polyquaternary ammonium salt, carboxymethyl fiber, polymaleic anhydride, gelatin, polyvinyl alcohol, polyethylene glycol and polyacrylamide. The polyquaternary ammonium salt, carboxymethyl fiber, polymaleic anhydride, gelatin, polyvinyl alcohol and polyethylene glycol are all water-soluble polymers. By selecting the water-soluble polymers, the obtained chemical sand-fixing material has good thermal stability and excellent durability. At the same time, by compounding the water-soluble polymers, the obtained chemical sand-fixing material has high strength and good wind erosion resistance after crusting. Polyacrylamide is a viscosity regulator, which is used to adjust the viscosity of the chemical sand-fixing material before crusting, so that the chemical sand-fixing material has good permeability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical sand fixation, and in particular to a chemical sand fixation material and a use method thereof. Background Art

[0002] Some desertified areas lack vegetation protection, and the phenomenon of sand and dust is relatively serious. Take the Taklimakan Desert in Xinjiang as an example. The Taklimakan Desert in Xinjiang is the largest desert in my country and the second largest mobile desert in the world. The climate here is dry and windy, the ecosystem is extremely fragile, and major wind and sand hazards occur frequently. Especially since the development of oil and gas resources, strong winds and sand have gradually invaded major oil facilities and buried major transportation routes, posing a serious threat to the safe operation of oil and gas resource exploitation.

[0003] Among the current measures for preventing and controlling wind and sand hazards, there are three methods, namely physical, chemical and biological sand control, according to the different materials used. Physical sand control is difficult to form sand quickly due to the problems of materials, transportation, cost and economy; biological sand control is also difficult to solve due to the limitation of environmental conditions and water resources. With the development of technology, chemical sand fixation has received extensive attention from the academic and engineering circles in recent years. The chemical sand fixation method mainly uses chemical materials and processes to construct a consolidation layer on the surface of the quicksand that can both prevent wind erosion and retain water, thereby playing a role in preventing and controlling sand. The advantages of this method are: (1) high construction efficiency and fast sand fixation; (2) an effective "sand cross section" can be formed near important facilities, thereby solving the problem of wind and sand deposition in traditional physical sand control methods; (3) the overall solidification and water retention of the dune surface are conducive to the growth of dune plant roots, thereby accelerating the process of desert ecological restoration.

[0004] Among them, chemical sand-fixing materials are divided into inorganic sand-fixing materials and organic sand-fixing materials. The existing inorganic sand-fixing materials are mainly water glass, cement, and gypsum, and the organic sand-fixing materials are mainly asphalt emulsion and lignin. Unfortunately, due to the inherent high temperature and water shortage in desert areas, high salt content in water, long sunshine hours, and high wind levels, the existing organic sand-fixing materials and inorganic sand-fixing materials cannot meet the requirements of desert sand fixation for wind erosion resistance, high temperature resistance, and high crust strength, so that chemical sand-fixing methods have never been fully promoted and applied in desert areas. Summary of the invention

[0005] The main purpose of the invention is to provide a chemical sand-fixing material and a method of using the same, aiming to solve the problem that the existing chemical sand-fixing materials cannot meet the requirements of desert sand fixation.

[0006] To achieve the above object, the present invention provides a chemical sand-fixing material, which comprises the following components:

[0007] Polyquaternium, carboxymethyl cellulose, polymaleic anhydride, gelatin, polyvinyl alcohol, polyethylene glycol and polyacrylamide.

[0008] Optionally, in the chemical sand-fixing material, the mass fractions of each component are:

[0009] 1-15 parts of polyquaternium salt, 5-25 parts of carboxymethyl cellulose, 1-20 parts of polymaleic anhydride, 2-15 parts of gelatin, 1-18 parts of polyvinyl alcohol, 1-15 parts of polyethylene glycol, and 2-20 parts of polyacrylamide.

[0010] Optionally, the chemical sand-fixing material further comprises an auxiliary agent, wherein the auxiliary agent comprises at least one of a reinforcing agent, an antioxidant, an ultraviolet light absorber and an ultraviolet light shielding agent.

[0011] Optionally, the antioxidant includes at least one of antioxidant 1135, antioxidant 1520 and antioxidant BNX1000.

[0012] Optionally, the ultraviolet light absorber includes at least one of ultraviolet light absorber 9510, ultraviolet light absorber Uv-106, and ultraviolet light absorber Uv-1130.

[0013] Optionally, the mass ratio of the polyquaternary ammonium salt to the auxiliary agent is 1-15:1-25.

[0014] Optionally, the auxiliary agent includes an enhancer, an antioxidant, an ultraviolet light absorber and an ultraviolet light shielding agent, and the mass ratio of the enhancer, the antioxidant, the ultraviolet light absorber and the ultraviolet light shielding agent is 1-8:1-5:1-5:1-5.

[0015] Furthermore, the present invention also provides a method for using a chemical sand-fixing material, comprising the following steps:

[0016] Dissolving the chemical sand-fixing material as described above in water at 50-80° C. to obtain a polymer aqueous solution;

[0017] The polymer aqueous solution is sprayed onto the surface of the quicksand to be treated.

[0018] Optionally, the mass ratio of the chemical sand-fixing material to water is 1:100-1000.

[0019] In the technical solution provided by the present invention, the raw material components of the chemical sand-fixing material include polyquaternary ammonium salt, carboxymethyl fiber, polymaleic anhydride, gelatin, polyvinyl alcohol, polyethylene glycol and polyacrylamide, wherein the polyquaternary ammonium salt, carboxymethyl fiber, polymaleic anhydride, gelatin, polyvinyl alcohol and polyethylene glycol are all water-soluble polymers. By selecting the above water-soluble polymers, the prepared chemical sand-fixing material has good thermal stability and excellent durability; at the same time, by compounding the above water-soluble polymers, the prepared chemical sand-fixing material has high strength and good wind erosion resistance after crusting; polyacrylamide is a viscosity regulator, which is used to adjust the viscosity of the chemical sand-fixing material before crusting, so that the permeability of the chemical sand-fixing material is good. DETAILED DESCRIPTION

[0020] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0021] In addition, the meaning of "and / or" appearing in the full text includes three parallel solutions. Taking "A and / or B" as an example, it includes solution A, solution B, or a solution that satisfies both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in this field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0022] Due to the inherent high temperature and water shortage in desert areas, high salt content in water, long sunshine hours and high wind levels, the existing organic and inorganic sand-fixing materials cannot meet the requirements of desert sand fixation for wind erosion resistance, high temperature resistance, and high crust strength. As a result, chemical sand fixation has not been fully promoted and applied in desert areas.

[0023] In view of this, the present invention proposes a chemical sand-fixing material. In one embodiment, the chemical sand-fixing material includes the following components: polyquaternary ammonium salt, carboxymethyl fiber, polymaleic anhydride, gelatin, polyvinyl alcohol, polyethylene glycol and polyacrylamide.

[0024] Among them, polyquaternary ammonium salts, carboxymethyl fiber, polymaleic anhydride, gelatin, polyvinyl alcohol, and polyethylene glycol are all water-soluble polymers. Under the desert sunshine temperature (≤80°C), these polymer materials have good thermal stability. In addition, these materials will not degrade or the degradation time is very long in a dry environment, and they have excellent durability.

[0025] The sand-fixing principle of the chemical sand-fixing material is as follows: dissolve the chemical sand-fixing material in water to obtain a polymer aqueous solution, spray the polymer aqueous solution onto the surface of the sand body, and the polymer aqueous solution will penetrate into the sand body under the action of gravity. At the same time, the polymer aqueous solution will gradually evaporate water on the surface of the dry sand body. After the water evaporates, the water-soluble polymer will become a gelled phase, thereby gelling the surface sand into a sand / polymer shell layer with a certain thickness, so as to play the role of chemical sand fixation.

[0026] In the technical solution provided by the present invention, the raw material components of the chemical sand-fixing material include polyquaternary ammonium salt, carboxymethyl fiber, polymaleic anhydride, gelatin, polyvinyl alcohol, polyethylene glycol and polyacrylamide, wherein the polyquaternary ammonium salt, carboxymethyl fiber, polymaleic anhydride, gelatin, polyvinyl alcohol and polyethylene glycol are all water-soluble polymers. By selecting the above water-soluble polymers, the prepared chemical sand-fixing material has good thermal stability and excellent durability; at the same time, by compounding the above water-soluble polymers, the prepared chemical sand-fixing material has high strength and good wind erosion resistance after crusting; polyacrylamide is a viscosity regulator, which is used to adjust the viscosity of the chemical sand-fixing material before crusting, so that the permeability of the chemical sand-fixing material is good.

[0027] After repeated tests by the inventors, it was concluded that preferably, the chemical sand-fixing material includes the following components in proportions by mass: 1-15 parts of polyquaternary ammonium salt, 5-25 parts of carboxymethyl fiber, 1-20 parts of polymaleic anhydride, 2-15 parts of gelatin, 1-18 parts of polyvinyl alcohol, 1-15 parts of polyethylene glycol, and 2-20 parts of polyacrylamide. In this way, the obtained chemical sand-fixing material has good permeability and high strength after shelling.

[0028] Polyacrylamide is a viscosity regulator, which is used to adjust the viscosity of the chemical sand-fixing material before it is shelled, so as to obtain shells of different thicknesses. By adding the polyacrylamide in the above ratio, the viscosity of the chemical sand-fixing material before it is shelled is appropriate. In this way, on the one hand, the permeability of the chemical sand-fixing material is good, and on the other hand, it is ensured that the polymer aqueous solution will not directly penetrate into the deep part of the sand body in a very short time (water does not have time to evaporate), thereby obtaining a sand / polymer shell with sufficient strength and thickness.

[0029] Furthermore, the molecular weight of the polyacrylamide is 5 million to 20 million. When the wind force level of the application scenario of the chemical sand-fixing material is low, the shell thickness can meet the conditions. If the shell thickness is set too thick at this time, it will waste materials; when the wind force level of the application scenario of the chemical sand-fixing material is high, if the shell thickness is set too low at this time, it cannot meet the sand-fixing requirements. The present invention does not limit the specific addition amount and molecular weight of polyacrylamide, and can be adaptively adjusted according to the wind force level of the actual application scenario to obtain a shell with a suitable thickness. In this way, not only the cost of chemical sand fixation is low, but also the sand fixation effect is good.

[0030] In order to improve the performance of the chemical sand-fixing material, in the present embodiment, the chemical sand-fixing material further comprises an auxiliary agent, and the auxiliary agent comprises at least one of a reinforcing agent, an antioxidant, an ultraviolet light absorber and an ultraviolet light shielding agent.

[0031] The durability of the chemical sand fixation material can be improved by adding an antioxidant. In this embodiment, the antioxidant includes at least one of antioxidant 1135, antioxidant 1520 and antioxidant BNX1000. The above antioxidants are all liquid antioxidants with good anti-aging effect.

[0032] Ultraviolet light absorber (i.e., UV absorber) is a light stabilizer with a wide range of ultraviolet absorption properties. In the present embodiment, the ultraviolet light absorber includes at least one of ultraviolet light absorber 9510, ultraviolet light absorber Uv-106, and ultraviolet light absorber Uv-1130. It should be noted that when the ultraviolet light absorber and the antioxidant are compounded, a synergistic effect can be produced, thereby improving the weather resistance and thermal stability of the chemical sand fixation material. In addition, the ultraviolet light shielding agent uses a physical method to block ultraviolet rays, and the ultraviolet light absorber uses a chemical method to preferentially react and reduce the impact of ultraviolet rays on material properties. By compounding the ultraviolet light absorber and the ultraviolet light shielding agent, the thermal stability can be improved.

[0033] The addition of additives can improve certain properties of chemical sand-fixing materials, but the addition of additives may also have certain adverse effects on chemical sand-fixing materials. Therefore, the addition of additives is not necessarily better. In this embodiment, the mass ratio of the polyquaternary ammonium salt to the additive is 1-15:1-25, so that the comprehensive performance of the obtained chemical sand-fixing material is the best.

[0034] Preferably, the auxiliary agent includes an enhancer, an antioxidant, an ultraviolet light absorber and an ultraviolet light shielding agent, and the mass ratio of the enhancer, antioxidant, ultraviolet light absorber and ultraviolet light shielding agent is 1-8: 1-5: 1-5: 1-5. The present invention does not limit the specific type of the enhancer. In this embodiment, the enhancer is a silicate aqueous solution.

[0035] In a preferred embodiment, the chemical sand-fixing material includes the following components in parts by weight: 1-15 parts of polyquaternary ammonium salt, 5-25 parts of carboxymethyl fiber, 1-20 parts of polymaleic anhydride, 2-15 parts of gelatin, 1-18 parts of polyvinyl alcohol, 1-15 parts of polyethylene glycol, 2-20 parts of polyacrylamide, 1-8 parts of enhancer, 1-5 parts of antioxidant, 1-5 parts of ultraviolet light absorber and 1-5 parts of ultraviolet light shielding agent. Under this ratio, the chemical sand-fixing material has the best strength after crusting, good wind erosion resistance, excellent thermal stability and durability, and the best comprehensive performance.

[0036] It should be noted that the present invention does not limit the preparation method of the chemical sand-fixing material. For ease of operation, in this embodiment, the raw material components of the chemical sand-fixing material are simply mixed.

[0037] On the basis of the above embodiments, the present invention further proposes a method for using a chemical sand fixation material. In one embodiment, the method comprises the following steps:

[0038] Step S10, dissolving the chemical sand-fixing material as described above in water at 50-80° C. to obtain a polymer aqueous solution.

[0039] Among them, the mass ratio of the chemical sand-fixing material to water is 1:100-1000, and the viscosity of the polymer aqueous solution can also be adjusted by controlling the amount of water added.

[0040] Step S20: spraying the polymer aqueous solution onto the surface of the quicksand to be treated.

[0041] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention, and are not used to limit the present invention.

[0042] Example 1

[0043] (1) The chemical sand-fixing material comprises the following components in parts by mass (where 1 part is 1 g): 15 parts of polyquaternary ammonium salt, 10 parts of carboxymethyl cellulose, 5 parts of polymaleic anhydride, 15 parts of gelatin, 18 parts of polyvinyl alcohol (molecular weight is 5 million), 10 parts of polyethylene glycol, 15 parts of polyacrylamide and 8 parts of reinforcing agent, wherein the reinforcing agent is a sodium silicate aqueous solution.

[0044] (2) The above components of the chemical sand-fixing material are mixed and then dissolved in water at 60° C. to obtain a polymer aqueous solution, wherein the mass ratio of the chemical sand-fixing material to water is 1:100.

[0045] (3) Spraying the above polymer aqueous solution onto the surface of the quicksand to be treated at an ambient temperature of 65° C. to obtain a sand / polymer shell layer.

[0046] After testing, the thickness of the obtained sand / polymer shell layer was 2 cm, and the mass loss rate in 5 minutes under force 11 wind was 0.3%.

[0047] Example 2

[0048] (1) The chemical sand-fixing material comprises the following components in parts by weight (where 1 part is 1 g): 1 part of polyquaternary ammonium salt, 15 parts of carboxymethyl cellulose, 20 parts of polymaleic anhydride, 10 parts of gelatin, 5 parts of polyvinyl alcohol, 15 parts of polyethylene glycol, 20 parts of polyacrylamide (molecular weight of 10 million), 5 parts of reinforcing agent, 2 parts of antioxidant, 1 part of ultraviolet light absorber and 5 parts of ultraviolet light shielding agent, wherein the reinforcing agent is sodium silicate aqueous solution, the antioxidant is liquid antioxidant 1135, and the ultraviolet light absorber is ultraviolet light absorber 9510.

[0049] (2) The above components of the chemical sand-fixing material are mixed and then dissolved in water at 50° C. to obtain a polymer aqueous solution, wherein the mass ratio of the chemical sand-fixing material to water is 1:200.

[0050] (3) Spraying the above polymer aqueous solution onto the surface of the quicksand to be treated at an ambient temperature of 65° C. to obtain a sand / polymer shell layer.

[0051] After testing, the thickness of the obtained sand / polymer shell layer was 1.5 cm, and the mass loss rate in 5 minutes under force 11 wind was 0.4%.

[0052] Example 3

[0053] (1) The chemical sand-fixing material comprises the following components in parts by weight (where 1 part is 1 g): 13 parts of polyquaternium salt, 5 parts of carboxymethyl cellulose, 10 parts of polymaleic anhydride, 10 parts of gelatin, 18 parts of polyvinyl alcohol, 10 parts of polyethylene glycol, 5 parts of polyacrylamide (molecular weight is 20 million), 8 parts of reinforcing agent, 1 part of antioxidant, 2 parts of ultraviolet light absorber and 3 parts of ultraviolet light shielding agent, wherein the reinforcing agent is sodium silicate aqueous solution, the antioxidant is liquid antioxidant BNX1000, and the ultraviolet light absorber is ultraviolet light absorber Uv-106.

[0054] (2) The above components of the chemical sand-fixing material are mixed and then dissolved in water at 80° C. to obtain a polymer aqueous solution, wherein the mass ratio of the chemical sand-fixing material to water is 1:1000.

[0055] (3) Spraying the above polymer aqueous solution onto the surface of the quicksand to be treated at an ambient temperature of 65° C. to obtain a sand / polymer shell layer.

[0056] After testing, the thickness of the sand / polymer shell layer was 3 cm, and the mass loss rate in 5 minutes under force 11 wind was 1.5%.

[0057] Example 4

[0058] (1) The chemical sand-fixing material comprises the following components in parts by weight (where 1 part is 1 g): 15 parts of polyquaternium salt, 25 parts of carboxymethyl cellulose, 1 part of polymaleic anhydride, 5 parts of gelatin, 15 parts of polyvinyl alcohol, 3 parts of polyethylene glycol, 8 parts of polyacrylamide (molecular weight is 15 million), 3 parts of reinforcing agent, 5 parts of antioxidant, 5 parts of ultraviolet light absorber and 1 part of ultraviolet light shielding agent, wherein the reinforcing agent is an aqueous solution of sodium silicate, the antioxidant is a liquid antioxidant 1520, and the ultraviolet light absorber is an ultraviolet light absorber 9510.

[0059] (2) The above components of the chemical sand-fixing material are mixed and then dissolved in water at 70° C. to obtain a polymer aqueous solution, wherein the mass ratio of the chemical sand-fixing material to water is 1:500.

[0060] (3) Spraying the above polymer aqueous solution onto the surface of the quicksand to be treated at an ambient temperature of 65° C. to obtain a sand / polymer shell layer.

[0061] After testing, the thickness of the sand / polymer shell layer was 1.5 cm, and the mass loss rate in 5 minutes under force 11 wind was 1.2%.

[0062] Example 5

[0063] Except that the mass ratio of the chemical sand-fixing material to water in step (2) is changed to 1:100, the remaining steps are the same as those in Example 2 to obtain a sand / polymer shell layer.

[0064] After testing, the thickness of the obtained sand / polymer shell layer was 1 cm, and the mass loss rate in 5 minutes under force 11 wind was 0.3%.

[0065] Comparative Example 1

[0066] Except that polyquaternium salt, polyacrylamide and carboxymethyl fiber are not added, the remaining steps are the same as those in Example 1 to obtain a sand / polymer shell layer.

[0067] After testing, the thickness of the obtained sand / polymer shell layer was 0.5 cm, and the mass loss rate in 5 minutes under force 11 wind was 5.6%.

[0068] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.

Claims

1. A chemical sand fixation material, characterized in that: Includes the following components: Polyquaternary ammonium salt, carboxymethyl cellulose, polymaleic anhydride, gelatin, polyvinyl alcohol, polyethylene glycol and polyacrylamide, wherein the mass fractions of each component are: 1-15 parts of polyquaternary ammonium salt, 5-25 parts of carboxymethyl cellulose, 1-20 parts of polymaleic anhydride, 2-15 parts of gelatin, 1-18 parts of polyvinyl alcohol, 1-15 parts of polyethylene glycol, and 2-20 parts of polyacrylamide.

2. The chemical sand-fixing material according to claim 1, characterized in that: The chemical sand-fixing material also includes an auxiliary agent, and the auxiliary agent includes at least one of a reinforcing agent, an antioxidant, an ultraviolet light absorber and an ultraviolet light shielding agent.

3. The chemical sand-fixing material according to claim 2, characterized in that: The antioxidant includes at least one of antioxidant 1135, antioxidant 1520 and antioxidant BNX1000.

4. The chemical sand-fixing material according to claim 2, characterized in that: The ultraviolet light absorber includes at least one of ultraviolet light absorber 9510, ultraviolet light absorber Uv-106 and ultraviolet light absorber Uv-1130.

5. The chemical sand-fixing material according to claim 2, characterized in that: The mass ratio of the polyquaternary ammonium salt to the auxiliary agent is 1-15:1-25.

6. The chemical sand-fixing material according to claim 2, characterized in that: The auxiliary agent comprises an enhancer, an antioxidant, an ultraviolet light absorber and an ultraviolet light shielding agent, and the mass ratio of the enhancer, the antioxidant, the ultraviolet light absorber and the ultraviolet light shielding agent is 1-8:1-5:1-5:1-5.

7. A method for using a chemical sand-fixing material, characterized in that: The following steps are involved: Dissolving the chemical sand-fixing material according to any one of claims 1 to 6 in water at 50 to 80° C. to obtain a polymer aqueous solution; The polymer aqueous solution is sprayed onto the surface of the quicksand to be treated.

8. The method for using the chemical sand-fixing material according to claim 7, characterized in that: The mass ratio of the chemical sand-fixing material to water is 1:100-1000.

Citation Information

Patent Citations

  • Chemical sand fixing agent and preparation method thereof

    CN102127453A

  • Preparation method for modified sand body

    CN103348837A

  • Method for governing deserts by utilizing modified sand

    CN103352459A

  • Solid dust suppressant

    CN104817997A

  • Chemical curing agent as well as preparation method and application thereof

    CN106635038A